2019
DOI: 10.1016/j.immuni.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Signature in Blood Reveals a Role for p53 in Regulating Malaria-Induced Inflammation

Abstract: Immunity that controls parasitemia and inflammation during Plasmodium falciparum (Pf) malaria can be acquired with repeated infections. A limited understanding of this complex immune response impedes the development of vaccines and adjunctive therapies. We conducted a prospective systems biology study of children who differed in their ability to control parasitemia and fever following Pf infection. By integrating whole-blood transcriptomics, flow-cytometric analysis, and plasma cytokine and antibody profiles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 69 publications
4
78
0
Order By: Relevance
“…Interestingly, in the present study, the differing cytokine, chemokine and growth factor levels detected in the non-infected individuals between 2010 and 2013 suggests that the impact of MTI could be beyond the response to P. falciparum infection at the time of the survey, suggesting that the rate of previous exposures could shape the basal immunological status. This difference in the basal immune system agrees with the observation by Tran et al [57] of a marked different transcriptomic and cellular profiles between malaria-protected and malaria-susceptible children prior to Plasmodium infection. This study also suggests that previous exposure to malaria, and possibly other pathogens or commensals, shape the basal immune system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, in the present study, the differing cytokine, chemokine and growth factor levels detected in the non-infected individuals between 2010 and 2013 suggests that the impact of MTI could be beyond the response to P. falciparum infection at the time of the survey, suggesting that the rate of previous exposures could shape the basal immunological status. This difference in the basal immune system agrees with the observation by Tran et al [57] of a marked different transcriptomic and cellular profiles between malaria-protected and malaria-susceptible children prior to Plasmodium infection. This study also suggests that previous exposure to malaria, and possibly other pathogens or commensals, shape the basal immune system.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, malaria exposure also induces changes in the innate immune response [55, 56]. A recent study identifies individuals who are primed to respond favorably to P. falciparum infection by controlling inflammatory symptoms (disease tolerance) and parasitaemia [57]. Accordingly, the lower levels of cytokines, chemokines and growth factors observed with increasing MTI could be reflecting a more controlled cellular response attributed to some degree of immuno-tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In the blood stage, high expression of p53 again appears as a protective factor against severe forms of malaria [ 116 ], being important not only to mitochondrial apoptosis, but also to limiting NF-κB-dependent proinflammatory cytokine induction [ 116 ]. Recently, a proteomic analysis of the malaria blood stage identified PfGARP as a parasite antigen, expressed in the early trophozoite stage [ 117 ]; the authors identified naturally acquired anti-PfGARP antibodies in the plasma of individuals resistant to malaria and these antibodies recognize the antigens in the surface of infected erythrocytes and direct the intra-erythrocytic parasites’ apoptosis-like cell death [ 117 ] ( Figure 2 C).…”
Section: Cell Deathmentioning
confidence: 99%
“…falciparum exposure, as children’s monocytes generally appear to return to a ‘non-tolerant’ steady-state baseline after the subsequent 6-month dry season [19]. However, a study in the same cohort found that children who are resistant to febrile malaria begin the malaria season with evidence of tolerized monocytes that upregulate p53, which is associated with attenuation of Plasmodium -induced inflammation [37]. Interestingly, a study conducted in a region of Uganda where P. falciparum transmission occurs year-round found that older children had a dampened pro-inflammatory serum cytokine response during acute malaria compared to younger children [38], consistent with the notion that ongoing exposure may be required to maintain a tolerant state in most children.…”
Section: Discussionmentioning
confidence: 99%